A identidade profissional do professor de Educação Física do ensino fundamental das escolas particulares de Castanhal, PA - SILVA, Thaynara Saldanha (2022)
The current study aimed to identify whether the teacher who works in the Private Education of the municipality of Castanhal, Pará, with the Physical Education (PE) discipline has an identity of its own in the area of study and it having as the initial and final grades of Elementary School as locus of this research, as well as being part of an ongoing project in the North region of Brazil that started in Basic Education. The research is qualitative and descriptive, that hat two moments, the first part was a bibliographic review and the second one was a field. The instrument adopted was the structured interview carried out with 17 teachers, it having as a guiding question: which professional identity(ies) do you assume as a school PE teacher in the private education? For data processing, the Content Analysis was adopted, through the Technique of Elaboration of Meaning Units. The results reveal that the interviewees did not have control over their own identity, considering that when answering the generating question, uncertainties were identified, generating conflicts and deviation from the central theme of the study. It was concluded that the undergraduate courses need special attention to the treatment related to the process of building the professional identity of future teachers, as well as the reformulation of the Pedagogical Projects of the Degree Courses in PE, since when they are going to enter the world of work, they can be aware of their identity.